What are the co-benefits of integrating climate change adaptation and mitigation in the energy sector: An empirical analysis focusing on the Namibian energy sector - Amesho, Kassian T. T (H. : ĐHKT, 2020)
The Namibian energy sector, and other energy sectors around the world, are presently in a period of rapid transformation that must include meaningful responses to climate change. The energy sector will also need to implement adaptation solutions to ensure the resilience of critical infrastructure to meet its regulatory obligations of reliability, which include aspects of resilience and security. Furthermore, the specter of climate change directly affects the resilience of energy infrastructure to the impacts of resource shortages or extreme weather. Non-climate issues affecting energy security and resilience in Namibia include declining low- cost energy generation options, increasing levels of demand from rising numbers of customers, variable output challenges from emerging renewable energy technologies, and increased pressures to avoid detrimental environmental impacts. Thus, promoting inclusive and sustainable economic and social development while concurrently adapting to climate change impacts and mitigating greenhouse gas emissions demands comprehensible policy approaches that span several sectors such as energy sector.